Effects of chemical and physico-chemical surface conditioning methods on the adhesion of resin composite to different mineral trioxide aggregate based cements. Issue 16 (18th August 2019) - Eyüboğlu, Tan Fırat; Olcay, Keziban; Özcan, Mutlu
Abstract: This study investigated the adhesion of resin composite to mineral trioxide aggregate based cements after different chemical and physico-chemical surface conditioning methods. Mineral trioxide aggregate based cements (Biodentine, ProRoot MTA, Imicryl MTA) were embedded in Teflon disks ( N = 180). After storing at 37 °C at 100% humidity for 72 h, substrate surfaces were polished using silicon carbide papers. Specimens were allocated to 3 groups to be conditioned with one of the following ( n = 15 per group): a) Adhesive resin (Clearfil SE Bond, CSE), b) Adhesive resin (Adper Single Bond 2, SB2), c) air-abrasion with 30 μm alumina coated with silica + silane + adhesive resin (ALB), d) no surface conditioning, control group (CON). Microhybrid resin composite (Filtek Z250) was applied on the conditioned substrate surfaces and photo-polymerized. After storage at 37 °C at 100% humidity for 24 h, adhesive interfaces were loaded under shear (1 mm/min) in a universal testing machine. After debonding failure types were analyzed. Data were analyzed using 2-way ANOVA and Tukey's test (alpha = 0.05). SBS results were significantly affected by surface conditioning ( p < 0.05) and materials ( p < 0.05). Interaction terms were significant ( p < 0.05). Biodentine-ALB resulted in significantly higher SBS values (3.96 ± 1.24) compared to those of other combinations, while ALB and SB2 resulted in no significant difference for ProRoot MTA and Imicryl MTA ( p > .05). CSE (1.36 ± 0.5- 1.98 ± 0.76) did not significantly increase SBS for all MTA materials compared to the control group (0.8 ± 0.52 – 2 ± 0.91) ( p > 9.05). While CON groups resulted in exclusively adhesive failures, ALB presented the highest incidence of mixed failures for all materials tested (60–100%).